La valoración de la prueba, en el delito de Asesinato por precio o promesa remuneratoria y su efecto jurídico en las Sentencias emitidas por los Tribunales de garantías penales de Chimborazo durante los años 2011-2013 - Barba Espinoza, Víctor Manuel (2015)
This research was made in the Court of Criminal Guarantees of Chimborazo, located in Riobamba, Chimborazo Province, this is part of the Judicial Council; its operation and organization is governed mainly by the Constitution and by the Organic Code of the Judiciary, here the processes are vented to be resolved by the judges. The standard of proof has been one of the most talked when issuing a sentence especially in those crimes against life, where shortcomings arise as a result of this is violation of the rights enshrined in the Constitution aspects. Finally many constitutional rights and guarantees may be affected by the fact that a judge does not consider all those items of evidence that can be presented process, so that today you found the Integral Code of Criminal Procedure, which ranks appear new offenses created and one of these hired killers which will be discussed in this thesis.